Anthropological approximation to safety in complex societies - Anton, Fina (Universidad Politécnica Salesiana (Ecuador), 2013)
Security is not just a strategy, but a need that results in a feeling from which people give meaning to each one of the actions that takes place both in the private and in the public fields, both individually and collectively. From this perspective, my contribution tries to analyse anthropologically how this concept relates with the modules of culture and so understand the current situation in complex societies.